The scope and impact of workplace diversity in the United Arab Emirates – A preliminary study - Al-Jenaibi, Badreya (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿Managing workplace diversity has become a priority concern among organizations in the United Arab Emirates (UAE) today. The UAE has one of the world's largest net migration rates, and the number of workers from India, the Philippines, Indonesia, Australia, the USA, among other countries, has increased significantly in recent decades. The UAE's cross-border mobility has resulted in the interaction of people with diverse language, customs and ethnic backgrounds. Although diversity has been shown to have a number of benefits, including enhanced employee creativity and competence, this recognition is often found more in theory than actual practice. Diversity can also lead to miscommunication, dysfunctional adaptation behaviours and the creation of barriers that reduce the benefits diversity can bring to the organization. Due to the nature of the UAE workplace, which is dominated by a foreign workforce, this study critically analyses the benefits organizations enjoy and the challenges they face in the diverse workplaces of the United Arab Emirates. The study used a multi-method approach combining survey data from 450 foreign workers with qualitative data from interviews with native officials of organizations. It is an attempt to compare the views of UAE workplace experience from two different groups—non-native workers and native officials. The research found a generally favourable view toward workplace diversity from the perspective of surveyed employees. However, when asked more detailed questions about company policy, a significant segment of respondents expressed reservations about their employer’s ability to implement successful intercultural communication and diversity practices.